2012
DOI: 10.1007/s00705-012-1476-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of enteroviruses associated with aseptic meningitis in children from India

Abstract: We identified and characterized enteroviruses associated with aseptic meningitis in children between April 2009 and March 2010. Enterovirus RNA was detected in 51 (45.5 %) of 112 CSF samples. Molecular typing by RT-PCR and sequencing of a partial VP1 region revealed the predominance of echovirus (ECV) 32 (n = 20), followed by ECV 11 (n = 10), ECV 13 and ECV 14 (n = 5 each), coxsackievirus (CV) B3 and CV B6 (n = 3 each), CV A2, CV A10 and ECV 30 (n = 1 each). Phylogenetic analysis of ECV 32 showed 0 to 4 % sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…E13, the predominant serotype, has been isolated rarely ( 3 , 10 ); however, nonpolio HEVs have been reported from India in connection with sporadic and epidemic meningitis/encephalitis cases ( 11 , 12 ). A wide spectrum of illnesses have been reported with E13 ( 13 ), so finding E13-associated AFP cases mimicking poliomyelitis ( 14 ) is not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…E13, the predominant serotype, has been isolated rarely ( 3 , 10 ); however, nonpolio HEVs have been reported from India in connection with sporadic and epidemic meningitis/encephalitis cases ( 11 , 12 ). A wide spectrum of illnesses have been reported with E13 ( 13 ), so finding E13-associated AFP cases mimicking poliomyelitis ( 14 ) is not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of previous studies have shown that HEVs are responsible for high percentages of all aseptic meningitis cases, ranging from 43 to 83% (Gharbi et al, 2006;Kumar et al, 2013;Papadakis et al, 2013 This copy is for personal use only -distribution prohibited.…”
mentioning
confidence: 99%
“…Globally, a genotype could be assigned to 58.0% of the specimens, with a clear relationship between the ability to type and the viral load. The overall sensitivity of the methods targeting the four A to D species of human EV on clinical specimens without cell culture amplification is not very high (approximately 50%), even when CODEHOP degenerated primers are used ( (this study). Several studies have reported higher typing performance either with a panel of specimens containing exclusively EV‐B strains or with species B‐specific primers .…”
Section: Discussionmentioning
confidence: 81%